Religion, conflict and post-secular politics - Haynes, Jeffrey (Routledge studies in religion and politics, 2020)
Religion, conflict and post-secular politics : an introduction -- Section 1: Religious actors and democracy -- Religion and democratisation : what do we now know? -- Democratisation in the Middle East and North Africa : what is the effect of globalisation? -- Islam and democracy in East Africa -- The "Arab Uprising", Islamists and democratisation -- Religion, democratization and secularization -- Section 2: Religion, human rights and civilisational interactions : postsecular politics and conflict -- Religion, democracy and civil liberties : theoretical perspectives and empirical ramifications -- Donald Trump, "Judeo-Christian values", and the "clash of civilisations" -- The United Nations alliance of civilisations and global justice -- The United Nations alliance of civilizations and interfaith dialogue : what is it good for? -- From Huntington to Trump : twenty-five years of the "clash of civilisations" -- Concluding reflections on religion, conflict and post-secular politics.